High-performance conductive silver paste and preparation method and application thereof
Through the use of high -performance silver paste in crystalline silicon solar cells, the positive electrode material with a stable network structure is prepared, the problem of photoelectric conversion efficiency caused by the acetic acid corrosion is solved, and the power generation efficiency and corrosion resistance of the battery are improved.
Patent Information
- Application Number
- CN202411309054.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-09
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-28
AI Technical Summary
The photoelectric conversion efficiency of the positive electrode material of crystalline silicon solar cells decreases under acetic acid corrosion, resulting in a decrease in power generation.
The high -performance conductive silver pulp is used to prepare raw materials including silver powder, aluminum powder, mixed glass powder and organic carriers. Through the cooperation of these materials, the positive electrode material forms a network formation and network intermediate, which improves its stability and corrosion resistance.
The photoelectric conversion efficiency of the positive electrode material of solar cells is improved, and the attenuation of the photoelectric conversion efficiency is reduced after the acetic acid corrosion, and the service life of the battery is extended.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery paste, and more specifically, to a high-performance conductive silver paste and a preparation method and application thereof. Background Art
[0002] With the development of society and the decreasing non-renewable energy, new renewable energy sources are gradually being widely used. As one of the clean new renewable energy sources, solar energy is used in solar cells, and crystalline silicon solar cells are being vigorously developed due to their high photoelectric conversion efficiency. At present, the positive electrode material of crystalline silicon solar cells is prepared by conductive silver paste, and most of the components in crystalline silicon solar cells are encapsulated by EVA. The EVA encapsulation material will decompose and produce acetic acid when exposed to the atmosphere and light conditions. Acetic acid will accelerate the corrosion of the silver electrode on the surface of the cell, reduce the efficiency of the cell, and reduce the power generation of the component. Therefore, the reduction of photoelectric conversion efficiency after acetic acid corrosion of the positive electrode material has become a problem to be solved in this field. Summary of the invention
[0003] In order to solve the problem of reduced photoelectric conversion efficiency after acetic acid corrosion of positive electrode materials in the related art, the present application provides a high-performance conductive silver paste and a preparation method and application thereof.
[0004] In the first aspect, the present application provides a high-performance conductive silver paste, which adopts the following technical solution: A high-performance conductive silver paste, the preparation raw materials of which include: 80-90wt% of silver powder, 0-2.5wt% of aluminum powder, 1-4wt% of mixed glass powder and 6-10wt% of organic carrier.
[0005] The silver paste described in the present application is formulated with silver powder, aluminum powder, mixed glass powder and an organic carrier, so that the positive electrode material prepared using the silver paste described in the present application forms a network former and a network intermediate, thereby ensuring that the positive electrode material has a stable structure and a good coordination state, avoiding a large amount of lead in the positive electrode material from being eluted, so that the positive electrode material has a good photoelectric conversion efficiency, and at the same time has the effect of less reduction in photoelectric conversion efficiency after acetic acid corrosion.
[0006] Preferably, the organic carrier comprises: 70-92 wt % of an organic solvent, 5-20 wt % of a high molecular polymer and 0.1-10 wt % of an organic carrier additive.
[0007] The present application can ensure that the mass ratio of the components of the organic carrier is limited. Preferably, the organic solvent is one or more of butyl carbitol, terpineol and tributyl citrate, the high molecular polymer is ethylene carbonate-acrylic acid copolymer, and the organic carrier additive is polyamide wax.
[0008] The present application limits the types of components in the organic carrier to ensure that the organic carrier is fully mixed with the silver powder, aluminum powder and mixed glass powder materials, thereby ensuring that the positive electrode material is preferably prepared in the subsequent preparation. The raw materials for preparing the mixed glass powder include 40-90% lead oxide, 5-30% boron oxide, 2-40% silicon oxide and 1-25% RO / R2O additives.
[0009] The present application utilizes lead oxide, boron oxide and silicon oxide as a mixed glass powder with RO / R2O additives to fill the gaps in the positive electrode material of the solar cell prepared with the silver paste glass powder, further improving the photoelectric conversion efficiency of the positive electrode material of the solar cell and reducing the reduced photoelectric conversion efficiency of the solar cell after acetic acid corrosion.
[0010] Preferably, the RO / R2O additive includes one or more of MoO3, WO3, V2O5, Nb2O5, Ta2O5, TiO2, ZrO2, HfO2, SiO2, TeO2, Al2O3, In2O3, Tl2O3, La2O3, ZnO, NiO, CuO, alkali and alkaline earth metal oxides.
[0011] The present application can ensure that the silver paste glass powder has good corrosion resistance by limiting the RO / R2O additive, thereby preventing the positive electrode material prepared with the silver paste glass powder from being corroded by the acetic acid solution in the battery.
[0012] Preferably, the D50 particle size of the high performance conductive silver paste is 0.8-1 micrometer, and the D90 particle size is 2.5-3.5 micrometers.
[0013] The present application limits the particle size of the high-performance conductive silver paste to ensure that the silver paste glass powder fills the gaps of the positive electrode when preparing the positive electrode material, thereby avoiding the degradation of the positive electrode performance due to the presence of unfilled gaps.
[0014] Preferably, the softening temperature of the high performance conductive silver paste is 300-500°C.
[0015] The present application can ensure that the glass powder has good performance when preparing the positive electrode material by limiting the softening temperature of the high-performance conductive silver paste.
[0016] In a second aspect, the present application provides a method for preparing a high-performance conductive silver paste, using the following technical solution: A method for preparing a high-performance conductive silver paste comprises the following steps: S1. Preparation of mixed glass powder: mixing lead oxide, boron oxide, silicon oxide and RO / R2O additives and heating them in a muffle furnace to obtain glass liquid, and then quenching, drying, grinding and drying them in sequence to obtain mixed glass powder; S2. Preparation of an organic carrier: mixing an organic resin, an organic solvent and an organic carrier additive, stirring the mixture under heating for 2 hours, and cooling the mixture to room temperature to obtain an organic carrier; S3. Preparation of high-performance conductive silver paste: silver powder, aluminum powder, the mixed glass powder and the organic carrier are mixed and ground, and the grinding is stopped when the slurry fineness is measured to be less than 5. The high-performance conductive silver paste is obtained after adjusting the viscosity.
[0017] The present application defines a method for preparing the high-performance conductive silver paste, thereby ensuring the performance of the high-performance conductive silver paste and improving the performance of the solar cell positive electrode material prepared using the high-performance conductive silver paste.
[0018] In a third aspect, the present application provides an application of a high-performance conductive silver paste in a positive electrode material for a solar cell.
[0019] The present application uses the high-performance conductive silver paste described in the above scheme or the high-performance conductive silver paste prepared by the preparation method described in the above scheme to be applied in the positive electrode material of solar cells. The positive electrode material prepared by the silver paste described in the present application can form a network former and a network intermediate, ensuring that the positive electrode material has a stable structure and a good coordination state, avoiding a large amount of lead in the positive electrode material from being eluted, and the positive electrode material can contact and bond with the corroded SiNx anti-reflection film layer in the positive electrode and the silicon of the lower layer, so that the silver particles precipitated by the reaction form silver-silicon contact points, thereby ensuring that the positive electrode has good electrical connection performance. In addition, during the acetic acid corrosion process of the positive electrode material, the positive electrode material provided by the present application can ensure that it is not decomposed by the reaction in a high temperature and high acid environment with a stable network structure, thereby ensuring that the positive electrode material described in the present application has good corrosion resistance.
[0020] In summary, this application has the following beneficial effects: 1. The present application limits the raw materials for preparing the high-performance conductive silver paste, and through the combination of silver powder, aluminum powder, mixed glass powder and organic carrier, enables the positive electrode material prepared using the silver paste of the present application to form a network former and a network intermediate, thereby ensuring that the solar cell positive electrode material prepared by the silver paste glass powder has good photoelectric conversion efficiency, and at the same time has the effect of less reduction in photoelectric conversion efficiency after acetic acid corrosion.
[0021] 2. In the present application, it is preferred to add RO / R2O additives to the high-performance conductive silver paste, because lead oxide, boron oxide and silicon oxide can form appropriate fluidity and a stable network structure with RO / R2O additives, further reducing the photoelectric conversion efficiency of solar cells after acetic acid corrosion.
[0022] 3. The present application limits the preparation method of the high-performance conductive silver paste to ensure that the prepared high-performance conductive silver paste has good performance, so that the finally prepared solar cell positive electrode material has good performance, and at the same time makes the solar cell positive electrode material have a lower photoelectric conversion efficiency after acetic acid corrosion.
[0023] The present application is further described in detail below with reference to the embodiments. DETAILED DESCRIPTION
[0025] Preparation Example 1 The method for preparing mixed glass powder comprises the following steps: S1. Preparation of mixed glass powder: in terms of molar percentage, weigh 65.18% lead oxide, 8.04% boron oxide, 4.46% silicon oxide, 6.25% boron trioxide, 8.93% zinc oxide, 4.46% germanium oxide and 2.68% gallium oxide, mix the weighed raw materials and place them in a muffle furnace, heat them at 700°C for 1 hour, then increase the temperature to 1000°C and heat them for 1 hour to obtain a uniform glass liquid, place the uniform glass liquid in deionized water for water quenching, and then dry, grind and bake them in sequence to obtain a mixed glass powder.
[0026] Preparation Example 2 The difference between Preparation Example 2 and Preparation Example 1 is that the "weighing 65.18% lead oxide, 8.04% boron oxide, 4.46% silicon oxide, 6.25% boron trioxide, 8.93% zinc oxide, 4.46% germanium oxide and 2.68% gallium oxide" in Preparation Example 1 is replaced by "45.60% lead oxide, 4.80% aluminum oxide, 20.00% silicon oxide, 17.60% boron trioxide, 12.00% lithium carbonate".
[0027] Preparation Example 3 The difference between Preparation Example 2 and Preparation Example 1 is that the "weighing 65.18% lead oxide, 8.04% boron oxide, 4.46% silicon oxide, 6.25% boron trioxide, 8.93% zinc oxide, 4.46% germanium oxide and 2.68% gallium oxide" in Preparation Example 1 is replaced by "70.60% lead oxide, 2.63% aluminum oxide, 7.45% silicon oxide, 10.29% boron trioxide, 2.43% lithium carbonate, 6.60% zinc oxide".
[0028] Preparation Example 4 The method for preparing an organic carrier comprises the following steps: S2. Preparation of an organic carrier: 5 wt% of ethylene carbonate-acrylic acid copolymer, 47 wt% of butyl carbitol, 23.5 wt% of pinene alcohol, 23.5 wt% of tributyl citrate and 1 wt% of polyamide wax were weighed in percentage by mass; the weighed raw materials were mixed and stirred under heating conditions for 2 h, and then cooled to room temperature to obtain an organic carrier.
[0029] Example 1 The preparation method of high-performance conductive silver paste comprises the following steps S3. Preparation of high-performance conductive silver paste: by mass, weigh 88 parts of silver powder, 0.7 parts of aluminum powder, 2 parts of the mixed glass powder in Preparation Example 1, and 9.3 parts of the organic carrier in Preparation Example 3, mix and grind them. Stop grinding when the slurry fineness is measured to be <5, and adjust the viscosity to obtain a high-performance conductive silver paste.
[0030] Example 2 The difference between Example 2 and Example 1 is that the "weigh 88 parts of silver powder, 0.7 parts of aluminum powder, 2 parts of the mixed glass powder in Preparation Example 1, and 9.3 parts of the organic carrier in Preparation Example 3" in Example 1 is replaced by "weigh 90 parts of silver powder, 1.5 parts of aluminum powder, 2.5 parts of the mixed glass powder in Preparation Example 2, and 6 parts of the organic carrier in Preparation Example 4".
[0031] Example 3 The difference between Example 3 and Example 1 is that the "weigh 88 parts of silver powder, 0.7 parts of aluminum powder, 2 parts of the mixed glass powder in Preparation Example 1, and 9.3 parts of the organic carrier in Preparation Example 3" in Example 1 is replaced by "weigh 86 parts of silver powder, 2.5 parts of aluminum powder, 3.2 parts of the mixed glass powder in Preparation Example 3, and 8.3 parts of the organic carrier in Preparation Example 4".
[0032] Example 4 The difference between Example 4 and Example 1 is that the "weigh 88 parts of silver powder, 0.7 parts of aluminum powder, 2 parts of the mixed glass powder in Preparation Example 1, and 9.3 parts of the organic carrier in Preparation Example 3" in Example 1 is replaced by "weigh 88.8 parts of silver powder, 3.5 parts of the mixed glass powder in Preparation Example 1, and 7.7 parts of the organic carrier in Preparation Example 4".
[0033] Example 5 The difference between Example 5 and Example 1 is that the "weigh 88 parts of silver powder, 0.7 parts of aluminum powder, 2 parts of the mixed glass powder in Preparation Example 1, and 9.3 parts of the organic carrier in Preparation Example 3" in Example 1 is replaced by "weigh 90.8 parts of silver powder, 2.7 parts of the mixed glass powder in Preparation Example 2, and 6.5 parts of the organic carrier in Preparation Example 4".
[0034] Example 6 The difference between Example 6 and Example 1 is that the "weigh 88 parts of silver powder, 0.7 parts of aluminum powder, 2 parts of the mixed glass powder in Preparation Example 1, and 9.3 parts of the organic carrier in Preparation Example 3" in Example 1 is replaced by "weigh 86.7 parts of silver powder, 4 parts of the mixed glass powder in Preparation Example 3, and 9.3 parts of the organic carrier in Preparation Example 4".
[0035] Comparative Example 1 The paste G08 of N-type TOPcon battery - Shu Mingfei is selected as the conductive silver paste.
[0036] Performance testing The prepared slurry in Examples 1-6 was printed on a TOPCon cell, dried, sintered and cooled, and the prepared solar cell was placed in a sealed test container at 85°C containing a 10% acetic acid saturated potassium chloride solution for 8 hours. The photoelectric conversion efficiency before and after the test was compared, and the acetic acid attenuation rate was calculated. The test results are shown in Tables 1 and 2.
[0037] Table 1 Photoelectric conversion efficiency before test Table 2 Photoelectric conversion efficiency after test Comparative Example 1 25.01 13.6407 0.7140 0.0007 84.94 28.5% Where Rsh is the parallel resistance, Eta is the conversion efficiency, Isc is the short-circuit current, Voc is the open-circuit voltage, Rser is the series resistance, and FF is the fill factor.
[0038] It can be seen from Examples 1-6 and Comparative Example 1 and Tables 1 and 2 that the high-performance conductive silver paste provided by the present application has good photoelectric conversion efficiency and can have a lower acetic acid attenuation rate after being soaked in acetic acid. This is because the positive electrode material prepared using the silver paste provided by the present application forms a network former and a network intermediate by combining silver powder, aluminum powder, mixed glass powder and an organic carrier, and the RO / R2O additive can cooperate with lead oxide, boron oxide and silicon oxide to make the network structure of the positive electrode material more stable, thereby reducing the reduced photoelectric conversion efficiency of the solar cell after acetic acid corrosion.
[0039] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-performance conductive silver paste, characterized in that: The raw materials for preparing the high-performance conductive silver paste include, by weight: 80-90 parts of silver powder, 0-2.5 parts of aluminum powder, 1-4 parts of mixed glass powder, and 6-10 parts of organic carrier.
2. The high performance conductive silver paste according to claim 1, characterized in that: The organic carrier comprises: 70-92 wt % of an organic solvent, 5-20 wt % of a high molecular polymer and 0.1-10 wt % of an organic carrier additive.
3. The high performance conductive silver paste according to claim 2, characterized in that: The organic solvent is one or more of butyl carbitol, terpineol and tributyl citrate, the high molecular polymer is ethylene carbonate-acrylic acid copolymer, and the organic carrier additive is polyamide wax.
4. The high performance conductive silver paste according to claim 1, characterized in that: In terms of molar ratio, the raw materials for preparing the mixed glass powder include 40-90% lead oxide, 5-30% boron oxide, 2-40% silicon oxide and 1-25% RO / R2O additives.
5. The high performance conductive silver paste according to claim 4, characterized in that: In terms of molar ratio, the raw materials for preparing the mixed glass powder include 60-85% lead oxide, 10-25% boron oxide, 5-20% silicon oxide and 3-7% RO / R2O additives.
6. The high performance conductive silver paste according to claim 4 or 5, characterized in that: The RO / R2O additives include one or more of MoO3, WO3, V2O5, Nb2O5, Ta2O5, TiO2, ZrO2, HfO2, SiO2, TeO2, Al2O3, In2O3, Tl2O3, La2O3, ZnO, NiO, CuO, alkali and alkaline earth metal oxides.
7. The high performance conductive silver paste according to claim 1, characterized in that: The D50 particle size of the high-performance conductive silver paste is 0.8-1 micrometer, and the D90 particle size is 2.5-3.5 micrometers.
8. The high-performance conductive silver paste according to any one of claim 1, characterized in that: The softening temperature of the high-performance conductive silver paste is 300-500°C.
9. The method for preparing the high-performance conductive silver paste according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Preparation of mixed glass powder: mixing lead oxide, boron oxide, silicon oxide and RO / R2O additives and heating them in a muffle furnace to obtain glass liquid, and then quenching, drying, grinding and drying them in sequence to obtain mixed glass powder; S2. Preparation of an organic carrier: mixing an organic resin, an organic solvent and an organic carrier additive, stirring the mixture under heating for 2 hours, and cooling the mixture to room temperature to obtain an organic carrier; S3. Preparation of high-performance conductive silver paste: silver powder, aluminum powder, the mixed glass powder and the organic carrier are mixed and ground, and the grinding is stopped when the slurry fineness is measured to be less than 5. The high-performance conductive silver paste is obtained after adjusting the viscosity.
10. Use of the high-performance conductive silver paste according to any one of claims 1 to 8 or the high-performance conductive silver paste prepared by the preparation method according to claim 9 in positive electrode materials for solar cells.